Tingkat Pengetahuan Penggunaan Tanaman Obat Tradisional Sebagai Alternatif Pengobatan Pada Masyarakat Desa Wisata Bindu - Dewi Agustini, Ni Putu; Megawati, Fitria; Juliadi, Debby; Widiari, Ni Nyoman Sri (Usadha, 2023)
Public knowledge about the use of plants as medicine is mostly limited to hereditary knowledge as a form of interaction between the community and the environment, especially plants. Currently medicinal plants or herbal plants have been widely used in the medical or health fields. Today's society prefers to use products that come from nature for safety reasons. This study aims to determine the level of knowledge of the use of traditional medicine as an alternative treatment in the community of Bindu Tourism Village. The research method used is a descriptive survey method with a cross-sectional design where the research object is only observed once without any pre-test and post-test with data collection techniques using questionnaires distributed via online in Bindu Tourism Village. The data obtained from the research results were then processed by calculating the percentage of respondent answers. The results of the questionnaire data analysis obtained from 104 respondents showed that the people who had a good level of knowledge were 51 people (49%), 46 people (44%), and the level of knowledge in the poor category were 7 people (7%). The average value of knowledge from 104 respondents is 77% which is included in the range (76%-100%), so the level of knowledge of respondents is good.